The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/elan.200703877
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry as an Alternative Tool for Trace Metal Detection in Peloid Marine Sediments

Abstract: Here was demonstrated for the first time a possible application of abrasive stripping voltammetry in the direct measurement of trace metals in anoxic, sulfidic marine sediments (peloid mud) from a small and shallow (0.2 -1 m) marine lagoon in Central Dalmatia, Croatia. Trace amounts of sample compounds are transferred to the graphite electrode surface and electrochemical reduction or oxidation processes are followed by the cyclic voltammetry in seawater or 0.55 M NaCl as electrolyte. After a preelectrolysis at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Such behavior has been assigned to the complex voltammetry exhibiting characteristics of both adhered and solution phase electrochemistry involving oxidation/dissolution of adhered and reduced species [14]. During negative-going scans that were started from 0 V, a single peak appeared (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behavior has been assigned to the complex voltammetry exhibiting characteristics of both adhered and solution phase electrochemistry involving oxidation/dissolution of adhered and reduced species [14]. During negative-going scans that were started from 0 V, a single peak appeared (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We have encountered the problem of FeS solid phase electrochemistry when we investigated sulfidic natural samples at paraffin-impregnated graphite electrodes (PIGEs). It became evident that it is impossible to understand the behavior of these systems without a detailed study of the redox processes of different Fe, Fe(I), Fe(II) and FeS phases [14]. Recently, it has been shown that different particulate metal-sulfide species are electroactive on the HMDE by producing cathodic peaks situated at around À 1.0 V (vs. Ag/AgCl) i.e., situated similarly to ones reported for FeS aq species [15 -17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, during investigation of mercury electrode/sulfide anion/second metal ion system, it has been shown that different metal sulfide particles are electroactive on the Hg and paraffin impregnated graphite electrodes (PIGE) [20][21][22][23][24][25]. The results show the possibility of Hg electrode use for detection of calcogenide nanoparticles in natural samples by adsorptive cathodic stripping voltammetry [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…It is important to mention that released Mn(II) after some short time is expected to oxidize and form nonelectrolabile colloidal manganese (IV) hydrous oxides, which normally constitutes the main fraction of manganese in oxic waters. To have a more complete knowledge about the speciation of manganese in such a system reaching equilibrium, a combination of the presented technique with, e.g., voltammetric analyses of the solid phase as reported in [50,51] could be interesting.…”
Section: Environmental Applicationmentioning
confidence: 98%